Analysis of Contemporary Mufassir's Interpretation of Polygamy - Doholio, Siti; Mustaqimah, Mustaqimah; Khadhary, Muhammad (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2025)
The focus of this research is to analyze contemporary interpreters' interpretations of polygamy. The author utilizes a purely qualitative descriptive research approach through an interpretive literature study. Some contemporary commentators in Indonesia, such as Hasbi, believe that permission for polygamy is not forced except for people who really believe they can act fairly and avoid cheating, and if a wife is no longer able to fulfill her obligations as a wife, such as she is old or suffering from illness. According to Hamka, Surah al-Nisa verses 2, 3, and 4 have a close relationship. Hamka emphasized that this verse aims at monogamy, not polygamy, because, according to him, this verse is only a valuable lesson for its readers and is not to be done. Meanwhile, according to Wahbah, this verse discusses fair behavior and the prohibition of doing injustice to orphans and women if they are not able to give a dowry to an orphan, it is forbidden for him to practice polygamy.